'Study and Research Path' multi-approach learning of Theory of Machines and Mechanisms. (1st November 2020) - Bartolomé, E.; Ruete, R.
ABSTRACT: A Study and Research Path (SRP) is a model, based on the Anthropological Theory of the Didactic (ATD), which describes the inquiry processes that take place when a new, generating question (Q0 ) is considered. The investigation of the question through different study and inquiry approaches leads to a rooted tree sequence of derived questions and answers. In this work, we explore the potential of SRPs to enrich the learning of first-year's Engineering subjects. A specific project-based SRP for the subject 'Theory of Machines and Mechanisms' was designed, implemented and analysed, using the Didactic Engineering ATD tool. The six-month course revolved around the study of eight real machines and mechanisms found in a car, using multiple approaches (including research of information, experimentation with models, analytical and numerical simulations, discussion with peers etc). The designed SRP provided the course with a new raison d'être and helped overcoming certain problematic phenomena (algorithmisation and atomisation of problems) detected in the previous organisation. We discuss the adaptation of the students to the SRP, the changes in the learning processes based on the analysis of the media-milieu dialectics and the improvement of the subject-specific and transversal engineering skills.